Analisis Model Bisnis dan Strategi Ekspansi Franchise Makanan Cepat Saji di Indonesia Konteks Perubahan Gaya Hidup Urban - Ardhi, Decella; Natasya Suryanto; Denda Hasbi (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The shift in lifestyle patterns, particularly in urban areas, has driven rapid growth in the fast food industry in Indonesia. Many franchise businesses are chosen by the public because they offer proven systems that reduce the risk of failure. This study aims to analyze and examine the market expansion strategies implemented by fast food franchise brand owners in Indonesia. The focus of this study is a descriptive qualitative approach with case studies of several local and international fast food franchises. The methods used in this study include in-depth interviews, observation, and documentation to gather relevant data on the strategies employed. Successful franchises are influenced by several key factors, including strong brand equity, clear operational standards, and support systems provided by the franchiser to franchisees. Furthermore, the ability to adapt to local tastes is also an essential aspect in the success of expanding fast food franchises in Indonesia. The study also reveals that the utilization of digital media, selection of strategic locations, and partnerships with food delivery services are major drivers of market expansion strategies. The results of this study emphasize that fast food franchises looking to grow further need to implement product differentiation strategies to remain competitive in an increasingly crowded market. Product innovation is key for franchises to stay relevant and stand out from other brands. Additionally, continuous mentoring and evaluation of franchise partners are critical for ensuring sustainable and mutually beneficial collaborations. Overall, applying the right strategies and ensuring sustainability will ensure the success and broader market expansion of fast food franchises in Indonesia.